PENGARUH DANA BPUM, HUMAN CAPITAL, DAN DIGITAL MARKETING TERHADAP KINERJA UMKM: Studi pada Usaha Mikro Kecil dan Menengah di Kabupaten Malang - Andriani, Wulan Suci; Kartika, Kartika; Pangesti, Resha Dwi Ayu (Jurnal Manajemen dan Profesional, 2023)
Abstract: This research was conducted to determine the impact of BPUM, human capital, and digital marketing funding variables on the performance of MSMEs in Malang Regency. The research method used is descriptive statistical quantitative method with multiple regression analysis techniques. The total population used is 84,800 micro business actors. From the total population, the slovin formula is used to determine a minimum sample of 100 respondents. The number of samples obtained from distributing questionnaires directly obtained 106 respondent data with 3 outlier data. The research results showed that the BPUM and digital marketing funding variables had a significant effect on MSME performance, while the human capital variable had no significant effect on MSME performance in Malang Regency. Keywords: Productive Assistance for Micro Enterprises (BPUM), Human Capital, Digital Marketing, MSME Performance